'His brain was not working properly': the surrender of HMS Seal and the court-martial of Lieutenant-Commander Rupert Lonsdale, RN. (3rd July 2018) - Mackenzie, S. P.
ABSTRACT: The post-war court-martial of Lieutenant-Commander Rupert Lonsdale, skipper of a British submarine captured at sea by the German Navy eight months into the Second World War, resulted in a full acquittal. It has been widely assumed that this trial was a pro forma exercise mounted simply in order to absolve publicly a gallant officer who had found himself in an impossible situation, the final verdict being a foregone conclusion. This was not so. Under the terms of the Naval Discipline Act then in force it was a serious offence to surrender a vessel of the Royal Navy to the enemy if it could still be defended, and the former captain had already admitted to having surrendered HMS Seal without preparing to scuttle her. Given the undisputed central facts of the case, only the introduction at trial by the defence of an unprecedented argument – that a slow build-up of carbon dioxide inside the boat over many hours while it was stuck underwater had rendered its captain mentally incompetent at a critical time – allowed the Court to side with the accused. The outcome influenced later naval disciplinary proceedings and was eventually acknowledged in changes to armed forces law in the United Kingdom.